Synergies between low cost air connections in Porto and visitors and pilgrims to Galicia - González Gómez, Manuel; Pereiro, Xerardo (Revista Galega de Economía, 2021)
With the aim of contributing to improve the knowledge of the complementary relations in tourism between the two cross-border regions of Galicia and North of Portugal, this work studies the growth of low-cost air connections at Porto airport, the flow of pilgrims to Santiago de Compostela who set out from Portugal and the international tourist flow to Galicia. The methodology used is descriptive-comparative analysis and the cointegration test. The results suggest that the growth of connections of low-cost companies at the Sá Carneiro airport in Oporto have contributed to increasing the presence of international tourists in Galicia. At the same time, the growth of international tourists in Galicia has made the Porto airport more attractive increasing the operating capacity of low cost airlines. The analysis also shows that the flow of pilgrims to Santiago de Compostela from Portugal is the one that has grown the most of all the Caminos de Santiago, suggesting a positive effect of the Porto airport on this group of visitors, and vice versa, increasing the number of pilgrims using the Porto airport to ensure the profitability / viability of air connections.